WOMEN ENTREPRENEURSHIP IN INDIA: CRITICAL AND CHALLENGING FACTORS FOR DEVELOPMENT - Tyagi, Dr Anita (IJRDO - Journal of Social Science and Humanities Research, 2017)
This paper focuses on understanding of the critical factors impacting on women’s enterprise; the particular problems they face and challenges in developing their businesses. In addition to those problems faced by all small-scale entrepreneurs, it is commonly asserted that women frequently face the problems in the socio-economic environment in which they operate.. Political and economic transformations seem to be acquiring everywhere—as countries convert from command to demand economies, dictatorships move toward democracy, and monarchies build new civil institutions. These changes have created economic opportunities for women who wish to set up and operate their own businesses. The knowledge about woman in global scene and especially in India, also the paper explains about the status of woman entrepreneurs and the problems faced by them when they start and manage their own businesses in the competitive world of business environment.